STUDI EMPIRIS MENGENAI INDIKATOR - INDIKATOR YANG MAMPU MEMBERIKAN DAMPAK PADA NILAI PERUSAHAAN - Sheilia Clarita; Agustin Ekadjaja (Jurnal Paradigma Akuntansi, 2026)
The purpose of this observation was to determine the impact of liquidity, dividend policy and investment decisions on firm value. The independent variable in this study is company value. While the dependent variable in this study is liquidity, dividend policy and investment decisions. The sampling method and technique were purposive sampling Method and non-probability sampling techniques. The population of the research data were 81 companies, and a sample of 9 companies was obtained. The research data was processed using Microsoft Excel and SPSS 22. Based on the results of data analysis, it shows that: (1.) liquidity has an insignificant impact on firm value; (2.) dividend policy has a significant impact on firm value; and (3.) investment decisions has a significant impact on firm value.